2021
DOI: 10.1002/ps.6313
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, SAR, and putative mode of action of N‐benzyl‐2‐methoxybenzamides as potential bleaching herbicides

Abstract: BACKGROUND Herbicides acting on biosynthesis of plant pigments have contributed greatly to weed control in recent years. In our previous studies, 2‐methoxybenzamides were discovered as a novel type of lead compound for the development of bleaching herbicides. RESULTS A total of 67 benzamide analogues were synthesized and evaluated for herbicidal activity. The structure–activity relationship (SAR) revealed that a methoxyl substitution at the 2‐position of the benzoyl moiety is essential for the herbicidal activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…The isoxaflutole was set as a positive control, whose active ingredient in the plant was the native ligand 9R6502 (Activity grade B). Since HPPD inhibition herbicides affected weed photosynthesis by blocking tyrosine metabolism, which led to weed bleaching and death, the herbicidal efficiency and crop selectivity of these compounds were assessed in terms of their inhibitory effect on chlorophyll content in weeds and crops separately. As listed in Table S5, these three compounds (100 mg/L) contributed to relatively strong herbicidal activity on W-70 and poor impact against SF . W-70 was selected to identify the in vivo chlorophyll inhibition capacity of these compounds at concentrations of 5–100 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…The isoxaflutole was set as a positive control, whose active ingredient in the plant was the native ligand 9R6502 (Activity grade B). Since HPPD inhibition herbicides affected weed photosynthesis by blocking tyrosine metabolism, which led to weed bleaching and death, the herbicidal efficiency and crop selectivity of these compounds were assessed in terms of their inhibitory effect on chlorophyll content in weeds and crops separately. As listed in Table S5, these three compounds (100 mg/L) contributed to relatively strong herbicidal activity on W-70 and poor impact against SF . W-70 was selected to identify the in vivo chlorophyll inhibition capacity of these compounds at concentrations of 5–100 mg/L.…”
Section: Resultsmentioning
confidence: 99%
“…In previous study, N-(4-fluorobenzyl)-2-methoxybenzamide was discovered as a lead compound for bleaching herbicides in our lab. 16 Successive investigation on the SAR revealed that introducing methoxy groups at 5-position of benzoyl moiety is beneficial for the herbicidal activity of N-benzyl-2-methoxybenzamides.…”
Section: Chemistrymentioning
confidence: 99%
“…The newly discovered chemicals exhibited post‐emergence herbicidal activity against both broad‐leaf weeds and grass weeds, and they caused an apparent bleaching effect similar to that of HPPD and PDS herbicides. Structure–activity relationship (SAR) carried out successively revealed that the presence of ortho ‐methoxyl moiety is crucial for the herbicidal activity of N ‐benzyl‐2‐methoxybenzamides 16 . This discovery provided a promising chemical scaffold for the development of new bleaching herbicides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of PDS within plants could block the biosynthesis of carotene and lead to the accumulation of phytoene, which, in turn, would result in the photooxidation of the plant cell. Then, the treated plants would develop a unique whitening symptom on the new leaves, followed by the full whitening effect of the entire leaves, and finally, death [10,11].…”
Section: Introductionmentioning
confidence: 99%